2017
DOI: 10.3346/jkms.2017.32.7.1111
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Oropharyngeal Carriage Isolates ofNeisseria meningitidisin Healthy Korean Adolescents in 2015

Abstract: The meningococcus carriage rate is age-dependent, with a high prevalence in adolescents and young adults. This cross-sectional study aimed to estimate the oropharyngeal carriage rate of meningococcus among healthy Korean adolescents and its relationship with several population characteristics. The survey was conducted from April to May 2015 among 1,460 first-year high-school students in 9 high schools located in Gyeonggi province, Korea. Each student answered a short questionnaire assessing risk factors for ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…The emergence of hypervirulent serogroup C (ST-11) led to the introduction of a meningococcal conjugate vaccine programme for serogroup C in Europe 29 , and the reduced proportion of serogroup C caused the proportion of serogroup B to increase 8 , 28 . It remains unclear if the emergence of one serogroup B infection belonging to B:P1.12-1, 1:F4-27:ST-44(cc41/44) in military trainees in 2015 resulted from the serogroup shifting due to vaccination, but serogroup B belonging to cc41/44 could be found in healthy South Korean adolescents in 2015 30 . Further surveillance and the introduction of a vaccine for serogroup B may be required when the prevalence of serogroup B in both patients and carriers is considered in South Korea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence of hypervirulent serogroup C (ST-11) led to the introduction of a meningococcal conjugate vaccine programme for serogroup C in Europe 29 , and the reduced proportion of serogroup C caused the proportion of serogroup B to increase 8 , 28 . It remains unclear if the emergence of one serogroup B infection belonging to B:P1.12-1, 1:F4-27:ST-44(cc41/44) in military trainees in 2015 resulted from the serogroup shifting due to vaccination, but serogroup B belonging to cc41/44 could be found in healthy South Korean adolescents in 2015 30 . Further surveillance and the introduction of a vaccine for serogroup B may be required when the prevalence of serogroup B in both patients and carriers is considered in South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Further surveillance and the introduction of a vaccine for serogroup B may be required when the prevalence of serogroup B in both patients and carriers is considered in South Korea. It is also possible that the emergence of serogroup E and serogroup non-typeable isolates may be associated with the partial application of a vaccine programme, even though serogroup E and non-groupable isolates tend to be common in asymptomatic carriage in healthy adolescents (E 12.2% and non-typeable 30.6) 30 . In our study, two IMD cases caused by serogroup E occurred in cancer patients who were immunocompromised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Carriage of serogroup B meningococci is also high in South Korea, with a carriage rate of 24.5% reported among 1460 first grade high school students (aged 16-17) in 2015. 18 Serogroup W circulation is significant across the Asia-Pacific region. Based on PCR testing, the Philippines reported that 16.7% ( n = 8/48) of blood and cerebrospinal fluid (CSF) specimens collected in 2018 were serogroup W. A higher percentage was reported in Australia during the first six months of 2019, with 25 out of 89 IMD cases (28%) being attributed to serogroup W (48% of these cases resulted in intensive care unit (ICU) admissions).…”
Section: Serogroup Distributionmentioning
confidence: 99%
“…A Coreia, por exemplo, apresenta baixa taxa de incidência de DMI (<2 casos/100.000 mil habitantes-ano) e baixa prevalência de portador de Nm (3,4%). A baixa prevalência de portadores pode ser atribuída a baixa incidência da DMI(KIM et al, 2017), ainda que essa relação não seja bem estabelecida.Além disso, a baixa prevalência de portadores pode ser explicada devido ao comportamento social dos adolescentes coreanos ser diferente dos adolescentes de outros países da Europa e das Américas.Não está claro na literatura o papel do contexto social em que os indivíduos vivem sobre a epidemiologia das NNP. Vimos que a epidemiologia dela é diferente da Nm quanto a distribuição etária, no entanto, residir em casa precária se mostra associado ao estado de portador de Nm e NNP.…”
unclassified